A modified Delphi consensus statement on the role of biopsy in small renal masses - Darryl E. Bernstein; Hannah Warren; Joseph Santiapillai; Geraldine Fox; William H. Wildgoose; Grant D. Stewart; Jim Armitage; Pieter Le Roux; Frank X. Keeley Jr; Nicholas Campain; Ben Challacombe; Hazel Warburton; et al. (BJUI Compass)
Abstract Objective To understand the variable utilisation of diagnostic biopsy for small renal masses (SRM) across the urology community, we worked with expert clinicians and patients to produce a consensus statement on the role of biopsy and to identify research gaps. Methods In phase I, qualitative interviews were performed to identify potential statements on the role of biopsy and research gaps. In phase II, an expert panel including patients scored statements on a 9‐point scale through a modified Delphi process involving three rounds of web‐based surveys. Consensus was considered to have been reached when 70% of participants scored a statement greater than or equal to seven. Panel members could propose additional statements for consideration after the first round. Following the second round, a moderation meeting was held to discuss statements where threshold of agreement was not met. Results In total, 35 participants were involved in this project and consisted of 23 clinicians and 12 patients, with 29 participants completing all three rounds. Overall, 18 statements reached consensus, 11 of which pertained to when and how a biopsy should be used in SRM management and 7 research recommendations to improve the evidence base for biopsy use. Conclusions and Clinical Implications This Delphi consensus statement, co‐produced by patients and clinicians, provides best‐practice guidance on the current role of renal tumour biopsy, including offering biopsy prior to active treatment if the outcome would affect management and offering a second attempt should the first biopsy be non‐diagnostic. Priority areas for future research included studies to evaluate how a biopsy affects choice of treatment and patient anxiety.